Penggunaan Semiotik dalam penghasilan karya Seni - Normala, Hj Omar (Universiti Malaysia Sarawak (UNIMAS), 2007)
In conveying art, the artwork should have beneficial function and context towards mankind. Images and texts are semiosis that possess meaning and create an effective visual communication. Pertaining to that, the use of semiotic in artwork attempt to invite audience to appreciate and think about the content being delivered.